When Diversity Works: The Effects of Coalition Composition on the Success of Lobbying Coalitions. Issue 3 (28th May 2019) - Junk, Wiebke Marie
Abstract: Lobbyists frequently join forces to influence policy, yet the success of active lobbying coalitions remains a blind spot in the literature. This article is the first to test how and when characteristics of active coalitions increase their lobbying success. Based on pluralist theory, one can expect diverse coalitions, uniting different societal interests, to signal broad support to policy makers. Yet, their responsiveness to this signal (i.e., signaling benefits) and contribution incentives within the coalition (i.e., cooperation costs) are likely to vary with issue salience. This theory is tested on a unique data set comprising 50 issues in five European countries. Results reveal a strong moderating effect of salience on the relationship between coalition diversity and success: On less salient issues, homogenous coalitions are more likely to succeed, whereas the effect reverses with higher salience, where diverse coalitions are more successful. These findings have implications for understanding political responsiveness and potential policy capture.